Does Preterm Prolonged Rupture of Membranes Increase the Risk of Needing Invasive Respiratory Support? A Retrospective Single-Centre Study - Eleanor Jeffreys; Ravindra Bhat; Anne Greenough; Theodore Dassios (MDPI AG, 2024)
(1) Background: Preterm premature rupture of membranes (PPROM) has been associated with increased perinatal morbidity, but the effect of PPROM on respiratory disease has not been previously quantified. We hypothesised that PPROM would be associated with a higher incidence of invasive ventilation. (2) Methods: A retrospective cohort study at the Neonatal Unit at King's College Hospital NHS Foundation Trust, London, UK, was conducted on infants born before 37 weeks of gestation. PPROM was defined as the rupture of membranes for >48 h. (3) Results: We reviewed 1901 infants (434 with PPROM) with a median (IQR) gestational age of 32.4 (28.7-35.0) weeks. The median (IQR) duration of rupture of membranes in the infants with PPROM was 129 (78-293) h. The incidence of invasive ventilation was 56% in the infants with PPROM and 46% in the infants without PPROM (p < 0.001). Following regression analysis, PPROM was significantly related to a higher incidence of invasive ventilation (odds ratio: 1.48; 95% CI: 1.13-1.92, adjusted p = 0.004) after adjusting for birth weight [odds ratio = 0.34; 95% CI: 0.33-0.43, adjusted p < 0.001], Apgar score at 10 min [odds ratio =0.61; 95% CI: 0.56-0.66, adjusted p < 0.001] and antenatal corticosteroid use (adjusted p = 0.939). (4) Conclusions: PPROM was associated with a 1.48-fold higher risk of needing invasive ventilation.